Characterization of multifunctional β-NaEuF4/NaGdF4 core–shell nanoparticles with narrow size distribution. Issue 5 (14th January 2016) - Schneider, Lilli; Rinkel, Thorben; Voß, Benjamin; Chrobak, Artur; Klare, Johann P.; Neethling, Jan; Olivier, Jaco; Schaniel, Dominik; Bendeif, El-Eulmi; Bondino, Federica; Magnano, Elena; Píš, Igor; et al.
Abstract : We characterized NaEuF4 /NaGdF4 core–shell nanoparticles. Abstract : The properties of β-NaEuF4 /NaGdF4 core–shell nanocrystals have been thoroughly investigated. Nanoparticles with narrow size distribution and an overall diameter of ∼22 nm have been produced with either small β-NaEuF4 cores (∼3 nm diameter) or large β-NaEuF4 cores (∼18 nm diameter). The structural properties and core–shell formation are investigated by X-ray diffraction, transmission electron microscopy and electron paramagnetic resonance, respectively. Optical luminescence measurements and X-ray photoelectron spectroscopy are employed to gain information about the optical emission bands and valence states of the rare earth constituents. Magnetic characterization is performed by SQUID and X-ray magnetic circular dichroism measurements at the rare earth M4, 5 edges. The characterization of the core–shell nanoparticles by means of these complementary techniques demonstrates that partial intermixing of core and shell materials takes place, and a significant fraction of europium is present in the divalent state which has significant influence on the magnetic properties. Hence, we obtained a combination of red emitting Eu 3+ ions and paramagnetic Gd 3+ ions, which may be highly valuable for potential future applications.